Experimental investigation of animals survival adequacy and efficacy in case of their soft tissues gunshot wounds using the thermometry technique - Lurin, I.; Khomenko, I.; Nehoduiko, V.; Tertyshnyi, S.; Vastyanov, R. (Journal of Education, Health and Sport, 2022)
The problem of gunshot wounds treatment is one of the urgent and incompletely resolved issues of modern surgery. Diagnosis of gunshot wounds is currently not efficient enough. There was a need to improve the content and scope of medical care with the possibility of strengthening its diagnostic chain. The aim of the work is to substantiate experimentally the feasibility and effectiveness of using diagnostic infrared thermometry in gunshot wounds of the soft tissues of the extremities. Experimental studies were performed under the chronic experimental conditions on Shinshilla breed rabbits which were subjected to gunshot wounds followed by laboratory, morphological and functional examination for 5 days. The animals were divided into 3 groups depending on the type of gunshot wound that was inflicted. The animals were removed from the experiment by the introduction of chloroethyl anesthesia on the 1st, 3rd and 5th days, after which the soft tissues with the capsule surrounding the fragment were subjected to histological and electron microscopic examination. On the 1st day of the study, a significant decrease in the diameter of the blood vessels of the affected area was determined in the group of animals that were subject to injury with firearms and metal fragments from the explosion of a grenade and an improvised explosive device. It was in these groups that the highest mortality rate was registered. Under the specified conditions of injury to the limbs of animals, as well as when injured by a pneumatic weapon with a temperature of fragments of 100 oC, pronounced changes in pulse and respiratory rate were noted. In further studies on rabbits on the 3rd and 5th days of the experiment, the actual results did not differ from those obtained 24 hrs after injury. Those rabbits that survived after the reproduction of various gunshot wounds had the greatest value. The results of their thermometric measurements were evaluated in the dynamics of experimental gunshot wounds and revealed the dependence of animal survival after gunshot wounds on the temperature of the limb in the area of the wound. There are the following leading criteria in favor of animals further survival after gunshot wounds - the presence of a perforating vessel in the area surrounding the affected space; the size of the diameter of the vessels in the adjacent area; no hemorrhage in the muscle tissue located near the affected area; comparable with normal data of the functional parameters of the animal's body – heart rate, blood oxygen pressure and respiration; thermometry results. The limb thermometry has the important prognostic value after their gunshot wound in terms of experimental animals survival. The correspondence of high thermometry indexes after a gunshot wound vs the higher risk of an animal death is statistically reliable and, accordingly, insignificant thermometric dynamics throughout the experiment is in favor of a positive outcome after injury. It is extremely important to evaluate thermometry data during the first 24 hours after receiving gunshot wounds, since we found out the maximum validity of this method in the early time intervals. All this, with adequate clinical testing and verification, has the most important medical prospects, aimed primarily at saving time for diagnostic measures and procedures. Thermometry allows to judge the activity and severity of connective tissue inflammation or sclerosis in the lesions of each wound and provides the possibility of clinical application of remote thermography as a non-invasive method of diagnosis and prediction of complications in wounded with gunshot and explosives in various wounds.